ANAEROBIC DIGESTER VARIATION FOR BIOGAS PRODUCTION ON COFFEE WASTEWATER TREATMENT - Elida Novita; Hendra Andiananta Pradana; Sri Wahyuningsih; Bambang Mahraenanto; Moh Wawan sujarwo; Moh. salman A. Hafidz (The University of Lampung, 2019)
Wet coffee processing methods will produce waste water containing organic matter. The high content of organic matter can be utilized as biogas through the anaerobic process. Biogas becomes renewable energy source. Anaerobic digesters construction can affect removal process of wastewater pollution and biogas quantity. The research aim’s was determine the performance biogas production of digester construction on conventional digester, CSTR and UASB from coffee waste water. The conventional digester worked without temperature control system, a UASB digester, and CSTR digester worked with temperature control system. Biomass volume was about 5 L with 35 days incubation time. The research result showed variation of biogas production on each digester. Based on the feeding variations, UASB has a stable performance with 83.57 ml/day of average biogas production. It has also highest remediation efficiency of COD, BOD and C/N with 85.00±0.34 %, 84.40%± 5.66 and 97.78± 0.57.